Versatile Approach for the Synthesis of Sequence-Defined Monodisperse 18- and 20-mer Oligoacrylates - Haven, Joris J; De Neve, Jeroen A; Junkers, Tanja (ACS macro letters, 2017)
Linear monodisperse 18- and 20-mer acrylates are obtained via consecutive synthesis of two sequence-defined acrylate 9- and 10-mers, followed by disulfide coupling utilizing reversible addition-fragmentation chain transfer (RAFT) end group chemistry. The sequence-defined oligoacrylates are accessed via consecutive single (SUMI) and multiple (MUMI) unit monomer insertions through RAFT polymerization, using the extensive acrylate monomer library as functional building blocks. Aminolysis of the trithiocarbonate macroRAFT end group and in situ oxidation of the thiols to form a disulfide bridge lead to the formation of 18- and 20-mer acrylates. In this approach, one or multiple acrylate building blocks can be inserted in each step by chain extension to form a stable carbon-carbon backbone. Isolation of the targeted monodisperse oligomers, from the statistical mixtures obtained at first, is performed by flash column chromatography with high efficiency. It is shown that the SUMI and MUMI strategy, when combined with flash column chromatography separation, is highly efficient and allows to construct monodisperse materials of very considerable length starting from cheap and very versatile building blocks.